Earth Science and the Law of the Sea: Keys to Canada's Offshore Energy and Mineral Resources beyond 200 Nautical Miles - Macnab, Ron; Haworth, Richard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary Article 76 of the United Nations Convention on the Law of the Sea allows Canadato establish sovereignty over resources o fthe seabed beyond the customary 200 nautical mile limit, when certain bathy-métrie and geological criteria are satisfied.This paper outlines the procedures formeeting those criteria, and describes the mutual benefits that can accrue to the earth sciences and the Law of the Seathrough programs for collecting and analyzing the necessary data. In the Atlantic and Arctic oceans, this work could allow Canada to extend energy and mineral jurisdiction into seabed areas that approach the size of the three Prairie Provinces combined.